Can sheep help to improve positive emotions, mindfulness, and self-efficacy expectancy? A pilot study of animal-assisted intervention as an enhanced CBT-based therapy for substance use disorders - Schmid, Petra; Nauss, Carmen; Jauch-Ederer, Claudia; Prinz, Petra; Tschöke, Stefan; Uhlmann, Carmen (Frontiers in Psychiatry, 2024)
Introduction: Substance use disorders (SUDs) are common and there is evidence of £ clinically significant benefit of cognitive behavioral therapy (CBT). The efficacy of ¤ CBT in SUDs has been confirmed, although relapse rates of 40-60% are reported. An ¥ enhancement of CBT-based therapy through an animal-assisted intervention (AAI) ¦ with sheep to normalize the occurrence of negative emotions and improve positive § emotions as well as mindfulness and self-efficacy expectancy was investigated. ¨Methods: A single session AAI with sheep in a group-setting was investigated © against treatment as usual over time. N=36 psychiatric inpatients with SUDs were examined by questionnaires before and one week after the intervention and ¡ additionally immediately after the intervention. ¡¡ Results: Positive emotions improved significantly in the AAI group one week after ¡£ the intervention with medium effect size; but not in the control group. Similarly, ¡¤ mindfulness and self-efficacy expectancy improved over time in the AAI group. When ¡¥ exploratory results are evaluated immediately after the intervention while still on the ¡¦ farm, the effects in favor of AAI are even larger. ¡ § Conclusions: AAI can thus be considered effective in improving positive emotions, ¡¨i mproving mindfulness and self-efficacy expectancy. The impressive effect sizes ¡© immediately after the intervention encourage to consider what can be done to ¡ maintain these even greater effect sizes over time.